Study On Bundung Grass (Scirpus Grossus L.) as The Natural Fibre For Fishing Gear Material With The Sinking Speed and Absorption Test - Zuldry, Andry; Syofyan, Irwandy; ', Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was held on march 2015, in fishing gear material labour of fisheries resource utilization program in fishery and marine science faculty.Aimed to find out sinking speed and absorption of bundung grass linne. meanwhile, the benefit of this research was as information material bundung grass utilization as material fishing. This research used experimental method. In this method, researcher tried to make an attempt and direct analysis of bundung grass linne potential as fishing gear material. The result of bundung grass linne research with length 4 cm, diameter 0,1 cm, spun direction Z, dry weight 0,05 gr showed that water absorption from bundung grass linne was 0,31 gr or 500 % from its own dry weight and has 2,6 cm/sec sinking speed. Based on absorption and sinking speed value from bundung grass, can be concluded that bundung grass has a potential as the natural fibre for fishing gear material.Keywords: Bundung grass, fishing gear material, sinking speed, absorption